Early evaluation of severity in patients with severe sepsis: a comparison with "septic shock" — subgroup analysis of the Japanese Association for Acute Medicine Sepsis Registry (JAAM‐SR). Issue 4 (27th July 2017) - Tarui, Takehiko; Yamaguchi, Yoshihiro; Suzuki, Koichiro; Tsuruta, Ryosuke; Ikeda, Hiroto; Ogura, Hiroshi; Kushimoto, Shigeki; Kotani, Joji; Shiraishi, Shin‐ichiro; Suzuki, Yasushi; Takuma, Kiyotsugu; Takeyama, Naoshi; et al.
Abstract : The subgroup analysis of the Japanese Association for Acute Medicine Sepsis Registry Advanced (JAAM‐SR‐Advanced) was conducted to identify early outcome indicators for severe sepsis. The novel combined criterion of initial hypotension and the worst lactate values ≥4 mmol/L within the initial 24 h is potentially useful as a single outcome predictor for severe sepsis. Abstract : Aim: The purpose of this subgroup analysis of a Japanese multicenter registry, the Japanese Association for Acute Medicine Sepsis Registry Advanced (JAAM‐SR‐Advanced), was to identify early outcome indicators for severe sepsis that are useful and more objective than "septic shock." Methods: Among 624 patients with severe sepsis registered in JAAM‐SR‐Advanced, 554 with valid serum lactate data were retrospectively studied. Hypotension before and after fluid resuscitation and the highest lactate values over the initial 24 h were compared for their ability to predict in‐hospital mortality. Results: Of the study group, 155 (28.0%) patients were non‐survivors and had significantly lower systolic blood pressures and higher lactate peaks. The mortality of 364 patients with initial hypotension was higher than those patients without it (32.7% versus 19.1%, P  <   0.01). Patients with the worst lactate values ≥4 mmol/L had much higher mortality than other patients ( P  <   0.001). In an attempt to predict outcomes, we combined initial hypotension and the worst lactate values. The patient group with initial hypotension and the worst lactate values ≥4 mmol/L (183 patients, 33.0%) had a significantly higher mortality rate of 48.6% than the other groups ( P  <   0.01). Conclusion: The novel combined criterion of initial hypotension and the worst lactate values ≥4 mmol/L within the initial 24 h is potentially useful as a single outcome predictor for severe sepsis.